Sarcasm Depiction of Ferdy Sambo's Object in Tempo Magazine: Pierce in Visual Signs - Prawianti, Marisa; Rizki Endi Septiyani; Mas’an Hamid (Jurnal Disastri (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2023)
This research aims to examine the use of sarcasm in the depiction of Ferdy Sambo objects in Tempo magazine. Pierce's semiotic approach is used as a theoretical framework to analyze the visual signs used to convey sarcasm. This investigation categorizes various types of signs in semiotics, including icons, indices and symbols, which appear in Ferdy Sambo's depiction of objects. In addition, this research explores the role of sarcasm as a communication strategy in expressing criticism of Ferdy Sambo's actions or attitudes regarding relevant social or political issues during that period. The research methodology used is qualitative analysis of two covers of Ferdy Sambo's special edition of Tempo magazine. The data collection process uses documentation methods, recording techniques, and screen capture methods. Based on the analysis findings, it appears Tempo magazine uses sarcasm when describing the Ferdy Sambo object, which shows a critical response to existing social and political problems. Sarcasm functions as a means of communication to express disagreement and criticism of Ferdy Sambo's behavior.